Secagem por micro-ondas na descontaminação de cascalhos de perfuração - Petri Júnior, Irineu (2014)
In the process of drilling, the rock fragments generated by the drill are taken from the well to the surface by the drilling fluid. The drilling fluid used in Brazil is made by synthetic oil, it presents several advantages over other types of drilling fluid. However, it has the disadvantage of having high toxicity and low biodegradability, requiring a separation system of drilled cuttings contaminated with this drilling fluid. Currently, the responsible equipment for reducing these levels to the permitted by law is working under extreme conditions and residual levels generated are very close to permitted by environmental legislation. For this reason, the technique of microwave drying has been studied for use in remediation of drilled cuttings and has shown very promising because it presents high efficiency and low operational problems when it is compared to conventional equipment. Therefore, the aim of this work are to investigate the influence of various operating parameters of a microwave dryer, analyze the efficiency of the dryer microwave suited for this job and to obtain operational conditions and information for operating a industrial microwave operating in continuous flow. So were tested influence of temperature, flow rate of inert, initial fluid content, reuse of drilled cuttings, rock type, fluid type and mechanical agitation in microwave drying; tests of drying kinetics and the mapping drying inside the microwave were made. The results showed no difference in drying with the influence of inert flow and the type of fluid, but there was influence of drying temperature, the initial salt content, initial fluid content and rock type. Drying with agitation can increased the removal efficiency in 17 % with 27 mm of bed thickness, rocks with slow heating improve the removal efficiency, drilled cuttings with similar physical aspects have similar removal efficiency. The heating of rocks in the microwave depends strongly of the oxides content in its composition. The temperature control of the bed should be the upper limit of the boiling range of the hydrocarbons present in the drilling fluid. The mapping study showed that there are drying gradients inside the microwave, besides showing the intrusive effect of metals in the material, effect of the edges of the recipes and the position of exhaust fan. The equipment showed to be as efficient as others listed in the literature, which can reduce the levels of n-paraffin to below 1 % by mass.